EMAP-II sensitize U87MG and glioma stem-like cells to temozolomide via induction of autophagy-mediated cell death and G2/M arrest. Issue 11 (3rd June 2017) - Yu, Qi; Liu, Libo; Wang, Ping; Yao, Yilong; Xue, Yixue; Liu, Yunhui
ABSTRACT: Despite the fact that temozolomide (TMZ) has been widely accepted as the key chemotherapeutic agent to prolong the survival of patients with glioblastoma, failure and recurrence cases can still be observed in clinics. Glioma stem-like cells (GSCs) are thought to be responsible for the drug resistance. In this study, we investigate whether endothelial monocyte-activating polypeptide-II (EMAP-II), a pro-inflammatory cytokine, can enhance TMZ cytotoxicity on U87MG and GSCs or not. As described in prior research, GSCs have been isolated from U87MG and maintained in the serum-free DMEM/F12 medium containing EGF, b-FGF, and B27. TMZ and/or EMAP-II administration were performed for 72 h, respectively. The results showed that TMZ combined with EMAP-II inhibit the proliferation of U87MG and GSCs by a larger measure than TMZ single treatment by decreasing the IC50 . EMAP-II also enhanced TMZ-induced autophagy-mediated cell death and G2/M arrest. Moreover, we found that EMAP-II functioned a targeted suppression on mTOR, which may involve in the anti-neoplasm mechanism. The results suggest that EMAP-II could be considered as a combined chemotherapeutic agent against glioblastoma by sensitizing U87MG and GSCs to TMZ.